Complexity of temperature dependence in methanogenic microbial environments - Conrad, Ralf (Frontiers in Microbiology, 2023)
There is virtually no environmental process that is not dependent on temperature. This includes the microbial processes that result in the production of CH4, an important greenhouse gas. Microbial CH4 production is the result of a combination of many different microorganisms and microbial processes, which together achieve the mineralization of organic matter to CO2 and CH4. Temperature dependence applies to each individual step and each individual microbe. This review will discuss the different aspects of temperature dependence including temperature affecting the kinetics and thermodynamics of the various microbial processes, affecting the pathways of organic matter degradation and CH4 production, and affecting the composition of the microbial communities involved. For example, it was found that increasing temperature results in a change of the methanogenic pathway with increasing contribution from mainly acetate to mainly H2/CO2 as immediate CH4 precursor, and with replacement of aceticlastic methanogenic archaea by thermophilic syntrophic acetate-oxidizing bacteria plus thermophilic hydrogenotrophic methanogenic archaea. This shift is consistent with reaction energetics, but it is not obligatory, since high temperature environments exist in which acetate is consumed by thermophilic aceticlastic archaea. Many studies have shown that CH4 production rates increase with temperature displaying a temperature optimum and a characteristic apparent activation energy (Ea). Interestingly, CH4 release from defined microbial cultures, from environmental samples and from wetland field sites all show similar Ea values around 100 kJ mol−1 indicating that CH4 production rates are limited by the methanogenic archaea rather than by hydrolysis of organic matter. Hence, the final rather than the initial step controls the methanogenic degradation of organic matter, which apparently is rarely in steady state.